NILAI PERUSAHAAN DALAM KAITANNYA DENGAN ARUS KAS BEBAS DAN PERTUMBUHAN PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Heny Rofizar; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2013)
The objective of this research is to examine the influence of free cash flow and firms growth both simultaneously and partially toward firms value. The research was conducted on listed companies from the manufacturing sector at the Indonesia Stock Exchange in 2008-2010. Based on the objective of this research, this research uses verificative research or hypotesis testing research by using census method. The target population in this research are manufacturing companies that have complete data for all variables studied. Based on the criteria mentioned, there are 111 firms-years (observations) that fulfill the population criteria during the three years of observation. The sources of data are secondary data obtained from financial statements that have been audited and share market price. All data are obtained from official website of Indonesia Stock Exchange (www.idx.co.id). Data are collected by using balanced panel data and analyzed by using multiple regression analysis.The results of this research show that: (1) simultaneously, free cash flow and firms growth have influence towards firms value, (2) partially, free cash flow and firms growth has positive influence towards firms value. Keywords: Free cash flow, Firms growth, Firms value